John Ross and Cultural Encounter: Translating Christianity in an East Asian Context. (26th May 2017) - Grayson, James H.
Abstract : John Ross, a late nineteenth-century missionary of the United Presbyterian Church of Scotland to Manchuria, was the effective founder of the Protestant Church in Korea through his translation of the New Testament into Korean. This article explores his work of translation by looking firstly at general issues in translating biblical texts into Korean, secondly at Ross's principles for translation, and thirdly how Ross actually conducted his translation work on a day-to-day basis. Thorough consideration will be given to the linguistic and social characteristics of the Korean language. The article concludes with an overview of the linguistic, religious and sociocultural effect of the 'Ross Translation'.